Introducing consulting services: Links to the provision of judicial accounting services in the environment of Saudi Arabia to reduce financial fraud (Entrepreneurship Journal for Finance and Business, 2024)
The study aimed to identify the effectiveness of applying "Consulting Services: links to the Provision of judicial accounting services" Standard. A field study on a random sample of judicial accountants, academic faculty members, and Certified Accountants, and Auditors in KSA is applied, by distributing questionnaire. It turns out that KSA environment is willingness to activate the role of judicial accounting considering the development standard (consulting services: links to the provision of judicial accounting services). Further, judicial accounting is considered a line of defense and prevention against fraud and financial corruption. The results also revealed a relationship between the factors that contribute to the activate the standard and the level of expected benefit from their application in the environment. Lastly, several recommendations are made, continue raising awareness among the local community in KSA about the importance of judicial accounting services. Also, monitoring and adaptation to the latest changes in the field of judicial accounting services, is crucial to maintaining a high level of effectiveness in implementing the standard.